The phenomenon of delocalisation in cyberspace and its influence on international dispute resolution - von Ondarza, Peter (Department of Commercial Law, 2023)
The rise of Cyberspace/the internet has opened a new source for legal issues. Beside issues of contract, tort, free speech, fundamental rights, privacy and anonymity, crime and security, intellectual property, governance and regulation, procedural issues are of predominant interest. This is because procedural law is the "last link" the chain in the exercise of state power. It follows that location-oriented, territory-oriented and sovereignty-oriented aspects play an important role in procedural provisions. Especially those aspects, however, seem to be most challenged by Cyberspace because of a new phenomenon: delocalisation.